The descent from the mountain: narrative patterns in Exodus 19-40 - Hauge, Martin R. (Journal for the study of the Old Testament, 2001)
This book traces a story of 'encounter' between divine and human, linked to 'the people' as the unlikely actors and made possible by the divine descent from mountain to camp. This 'close reading' of Exodus 19-40 focuses on the repetition of the 'encounter on the mountain'. This double encounter is expressed in a narrative structure of preparatory episodes climaxed by the theophany. The tension of the narrative is linked to 'the people' as the unlikely heroes of encounter and solved by the divine descent from the divine mountain to the man-made tent. The new situation of permanent encounter is foregrounded by the juxtaposed stories of pre- and post-Sinai journey, and the theme of the 'substitution of Moses' underlines a radical reinterpretation of traditional concepts, inviting the reader to embark on a process of identification.